RANCANG BANGUN BELT KONVEYOR ROTARY UNTUK PENGAYAKAN PASIR - Abd. Kadir; Bahdin Ahad Badia (Jurnal Multidisipliner Kapalamada, 2025)
This study aims to design and develop a rotary belt conveyor as a sand screening machine to improve the effectiveness of the screening process. The research method includes mechanical system design, frame analysis covering stress, strain, displacement, and safety factor, as well as simulation using Autodesk Inventor 2020. In addition, calculations of conveying capacity, material cross-sectional area, and sand screening rate per hour were performed. The frame simulation results under a load of 4,165 N using aluminum 6061 material show a maximum stress of 71.126 MPa (manual calculation) and 52.16 MPa (simulation), strain values of 0.001032 and 0.000635, maximum displacement of 0.4068 mm and 0.1912 mm, and safety factors of 3.8 and 5.2, respectively, indicating that the frame design is structurally safe. The designed rotary belt conveyor is capable of conveying and screening sand with a capacity of up to 5.7 tons/hour using a 2 HP electric motor. These results indicate that the developed rotary belt conveyor can serve as an effective mechanical solution for sand screening processes.